EFFECT OF PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION (PNF) IN IMPROVING SENSORIMOTOR FUNCTION IN PATIENTS WITH DIABETIC NEUROPATHY AFFECTING LOWER LIMBS (International Journal of Physiotherapy, 2016)
Background: Diabetic Mellitus is a group of metabolic disease characterized by hyperglycaemia resulting from defects in insulin secretion, insulin action or both. Distal Sensorimotor Polyneuropathy is the most common complication of diabetes which mainly affects the lower limbs. Most of the studies aimed at individually increasing muscle strength or sensation but not on overall performance enhancements of the diabetic lower limbs. The evidence supporting the effectiveness of PNF in diabetic neuropathic patients is scarce.Methods: 30 patients, with age between 50 to 70 years, diagnosed with Diabetic Sensorimotor Polyneuropathy (DSP) were selected from the department of Medicine and department of Neurosurgery Guru Gobind Singh Medical College and Hospital. Patients were evaluated at the beginning and at the end of the intervention using Diabetic Neuropathy Examination scores. Patients received 3 sets of exercises one hour/day with 3 days/week for 3 months. Each set of exercises consists of 5 repetitions of PNF patterns (alternate day) and techniques.Results: D1 & D2 patterns of PNF are effective in improving both motor and sensory functions of diabetic patients with neuropathic symptoms. Improvement in muscle strength, reflex and sensations occurred to a greater extent after the treatment of three months in these subjects. This study shows that PNF patterns were effective at enhancing sensorimotor problems of lower limbs.Conclusion: This study concluded that PNF is found to be effective in improving sensorimotor functions of diabetic neuropathic patients affecting lower limbs.